Using foreign material detection methods to assist the food industry - Ristau, Karen (Kansas State University, 2022)
Foreign material is a constant hazard of concern for the food and meat industries. Production facilities need to identify ways to detect foreign material for controlling, monitoring, and tracking foreign material in products. As the food industry continues to deal with an increase of foreign material contamination, the need to detect it becomes more important. It is imperative for food manufacturers to avoid foreign material in the finished product. In addition, food manufacturers need to consider what types of detection methods will be used and where they should be in the production system. Understanding the technologies will aid production facilities on how to use them for specific food products, and ultimately minimize the risk of physical hazards introduced through foreign material. Filtering and screening, metal detection, ultrasound technology, X-ray, and terahertz technologies were assessed for their usage and advantages and disadvantages. Filtering and screening use a type of barrier to remove foreign material from food products. Filters and screens are best used for dry or free-flowing products, but they are also helpful at the beginning of a production process. Metal detection is used for finding metal in food products. This technology has been shown to be highly effective and to work well with multiple processes. Ultrasound technology is a nondestructive detection method that uses thermal imagining to find differences. Ultrasound is effective for the dairy and nut industry, but it requires lots of time and data for initial set up. X-ray can detect different types of foreign material including metal and can be used for a variety of food products. Terahertz is like X-ray by using imaging to find the foreign material and is effective in meat products. The technologies reviewed can all be an effective method for detecting foreign material. Overall, X-ray was found to be the most effective detection method across all industries.
Keywords: Foreign material detection methods